2007
DOI: 10.1161/circulationaha.106.649038
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease and Other Heterotaxic Defects in a Large Cohort of Patients With Primary Ciliary Dyskinesia

Abstract: At least 6.3% of patients with PCD have heterotaxy, and most of those have cardiovascular abnormalities. The prevalence of congenital heart disease with heterotaxy is 200-fold higher in PCD than in the general population (1:50 versus 1:10 000); thus, patients with PCD should have cardiac evaluation. Conversely, mutations in genes that adversely affect both respiratory and embryological nodal cilia are a significant cause of heterotaxy and congenital heart disease, and screening for PCD is indicated in those pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
327
1
15

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(350 citation statements)
references
References 48 publications
7
327
1
15
Order By: Relevance
“…This result, in agreement with previous data [6], is lower than the classically reported proportion of situs inversus [5,7,17]. This discrepancy could be due to patient selection mainly based on the presence of chronic airway infections of unknown origin, but not necessarily associated with situs inversus.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result, in agreement with previous data [6], is lower than the classically reported proportion of situs inversus [5,7,17]. This discrepancy could be due to patient selection mainly based on the presence of chronic airway infections of unknown origin, but not necessarily associated with situs inversus.…”
Section: Discussionsupporting
confidence: 89%
“…Situs inversus associated with airway infections is the most suggestive condition justifying systematic TEM analysis of cilia. However, situs inversus is not constant in PCD [5][6][7]17] and ciliary studies are often proposed in the presence of upper and/or lower chronic airway infections of unknown origin. The strong relationship between the presence of a sinopulmonary syndrome and the detection of a main defect suggests that this syndrome could be a good clinical criterion to improve patient selection for TEM analysis of cilia.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PCD within the heterotaxic subclass is unknown [45] 40-50% of PCD patients present with situs inversus totalis (Kartagener's syndrome in PCD) [9] 6% show heterotaxy (situs ambiguus) [46] Mild fetal cerebral ventriculomegaly [47] Neonatal .75% of full-term neonates with PCD exhibit neonatal respiratory distress requiring supplemental oxygen for days to weeks [8,9] Continuous rhinorrhoea from the first day of life [48][49][50] Mirror-image organ arrangement and other forms of heterotaxy (see Antenatal rows above) [51] Hydrocephalus may occur in some individuals with PCD, and may reflect dysfunctional ependymal cilia [47,52,53] Childhood Chronic productive or wet-sounding cough, associated or not with recurrent atelectasis or pneumonia Atypical asthma that is nonresponsive to treatment, especially if a wet-sounding cough is present…”
Section: Pcd As An Associated Diagnosismentioning
confidence: 99%
“…Studies have used different definitions and classification systems for heterotaxy [12,[78][79][80][81][82][83], despite standardisation efforts [84]. While some authors group situs inversus and situs ambiguous under the umbrella of heterotaxy [82], others believe it should be restricted to situs ambiguous only [2,81,83,84].…”
Section: Cardiac Managementmentioning
confidence: 99%
“…While some authors group situs inversus and situs ambiguous under the umbrella of heterotaxy [82], others believe it should be restricted to situs ambiguous only [2,81,83,84]. Using the latter definition, KENNEDY et al [83] reported that over 6% of PCD patients presented with heterotaxy. This is believed to be an underestimation, as abdominal imaging and echocardiograms are not carried out routinely in PCD patients.…”
Section: Cardiac Managementmentioning
confidence: 99%